Simplified Design and Development of Radio-Tracking on Thai-Traditional Rocket (Bang Fai) With Real Case Experiments - Pirada Techavijit; Polkit Sukchalerm (My University, 2023)
Thousands of large-scale homemade rockets (Bang Fai) are fired during Thai rocket festival annually. To prevent harm to airspace and ground, this paper proposes the design and development of a radio-tracking system that can report the velocity and altitude in real-time. The design is simplified with its small size and inexpensive price but still works with the rocket's dynamics. This paper also reports the results of rockets' ascent/descent velocities and their altitudes from tracking system mounted on the rockets. All this data can be used for evaluating the airspace and ground risks and for improving the design for future developments.
Keywords: Radio Wave Propagation Studies; Millimeter-Wave Propagation and Modeling; Precipitation Measurement and Analysis